Portraiture, race, and subjectivity: the opacity of Marie-Guillemine Benoist's Portrait d'une négresse. Issue 1 (2nd January 2019) - Bishop, Cécile
Abstract: In 1800, between the first abolition of slavery by the French revolutionary government and its reinstatement in 1802, Marie-Guillemine Benoist exhibited a controversial painting known as Portrait d'une négresse (Portrait of a Negress). A rare example of a portrait focusing on a black woman, the painting has received two main interpretations: some art historians have hailed it as a humane, ennobling depiction of the sitter, while others have criticized its objectification of the black body. This article, by contrast, shows how the ambiguities of the portrait challenge the binary of subjecthood and objecthood that underpinned the enslavement of African subjects. Focusing on the treatment of the subject's skin, it confronts Benoist's painting with contemporary textual accounts of skin color and face, revealing how the opacity of the painting challenged the racialized and gendered codes through which bodies were imagined as indexes of subjectivity. The value of Benoist's painting, however, is not limited to its past meanings ; its opacity has ongoing relevance for our own engagement with portraiture. Building on Édouard Glissant's concept of opacity, I argue for an imaginative empathy beyond the desire fully to know or understand the other.